Analisis dan Simulasi Numerik Model Penyakit Diabetes Melitus di Kabupaten Pinrang Menggunakan Metode Runge-Kutta Orde 4 - St. Maryam; Try Azisah Nurman; Ilham Syata (Jurnal MSA ( Matematika dan Statistika serta Aplikasinya), 2024)
This study discusses the analysis and simulation of Diabetes Mellitus in Pinrang Regency by applying the used the Order 4 Runge-Kutta method. The type of research used is applied research which aims to apply the model and find out numerical solutions to the model in predicting diabetes cases mellitus in Pinrang Regency in the future. The mathematical model of Diabetes Mellitus is in the form of a system of non-linear differential equations which includes the variables (Susceptible), (Exposed), (Infected) and (Infected With Treatment). The research results obtained in 2023 with years using the Runge-Kutta method of order 4 with initial values ​​of , , and . The rate of the susceptible population has decreased due to the interaction of exposed individuals. The exposed individual population has also decreased while the infected population without treatment and those infected with treatment have increased then decreased.